IMPLEMENTASI SENSOR ULTRASONIK UNTUK HANDSANITIZER OTOMATIS (Fakultas Teknik Universitas Wisnuwardhana, 2022)
Hand sanitizer is something that really needs to be used today to keep hands clean from germs and viruses. Everyone uses hand sanitizer, either bringing their own or using those available in public places. However, hand sanitizers circulating in public places are still manual and used by many people which allows the spread of the virus to occur. Therefore, a tool is needed to help make automatic hand sanitizers that can reduce the potential for the spread of viruses and harmful germs. The tool that will be made is “Automatic Hand Sanitizer”. This tool is made to change the hand sanitizer work system that was previously manual to automatic, and is more clean. This tool works when the sensor detects the hand less is then 10 cm, then the motor dc will pull the lever and release the hand sanitizer.